2015
DOI: 10.1002/acr.22535
|View full text |Cite
|
Sign up to set email alerts
|

Policy‐Into‐Practice for Rheumatoid Arthritis: Randomized Controlled Trial and Cohort Study of E‐Learning Targeting Improved Physiotherapy Management

Abstract: Objective. To examine the effectiveness of a physiotherapy-specific, web-based e-learning platform, "RAP-el," in bestpractice management of rheumatoid arthritis (RA) using a single-blind, randomized controlled trial (RCT) and prospective cohort study. Methods. Australian-registered physiotherapists were electronically randomized into intervention and control groups. The intervention group accessed RAP-eL over 4 weeks. Change in self-reported confidence in knowledge and skills was compared between groups at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 31 publications
(54 reference statements)
1
48
0
17
Order By: Relevance
“…Evaluation can be undertaken at the level of specific components of MoCs (e.g. strategies to build workforce capacity in skills and knowledge to deliver best MSK care[43,45,47]); evaluation of implementation of MoCs at a system-wide programmatic level (e.g. an osteoarthritis care program[48]); and the evaluation ofMoCs at a system-wide level (e.g.…”
mentioning
confidence: 99%
“…Evaluation can be undertaken at the level of specific components of MoCs (e.g. strategies to build workforce capacity in skills and knowledge to deliver best MSK care[43,45,47]); evaluation of implementation of MoCs at a system-wide programmatic level (e.g. an osteoarthritis care program[48]); and the evaluation ofMoCs at a system-wide level (e.g.…”
mentioning
confidence: 99%
“…Amini et al stated that there is a certain relationship between perceived benefits and quitting smoking among the youth (23). In addition, in Australia, Fary et al stated that there was a significant relationship between perceived benefits and physical activities (24). Sharifirad et al revealed that by reducing perceived barriers, fewer teens started smoking (25).…”
Section: Discussionmentioning
confidence: 99%
“…Self‐rated confidence in OA management knowledge and clinical skills were measured using a customized battery of items based on a tool previously developed to measure the constructs in RA care . In the original tool, items were derived from a critical appraisal of RA clinical guidelines and an international Delphi study .…”
Section: Methodsmentioning
confidence: 99%
“…In the original tool, items were derived from a critical appraisal of RA clinical guidelines and an international Delphi study . Adequate measurement properties have been established for the tool, which has been applied in a clinical trial . For the current study, items from the original tool that were not RA‐specific and could be reasonably translated to OA care were retained (eg, principles of nonpharmacologic care, principles of chronic disease self‐management, application of diagnostic criteria, outcomes tools).…”
Section: Methodsmentioning
confidence: 99%